PEMBERDAYAAN MASYARAKAT DALAM MEMINTAS MATA RANTAI PENYEBARAN COVID-19 DENGAN PENDEKATAN PHBS (PERILAKU HIDUP BERSIH DAN SEHAT DI DESA MUARA BATUN KABUPATEN OGAN KOMERING ILIR (OKI) - Intan Kumalasari; Azwaldi Azwaldi; Eliza Eliza; Veratiwi Veratiwi; Itail Husna Basa (Universitas Muhammadiyah Tapanuli Selatan, 2021)
WHO declared the covid-19 outbreak an international public health emergency and declared a pandemic due to the alarming level of spread and severity of the outbreak. This virus causes illnesses ranging from the common cold to more severe illnesses such as acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS). It is estimated that by September 2020 more than 27.7 million confirmed cases of Covid-19 and 900 thousand deaths. Various attempts have been made to reduce the rate of spread of this corona virus. However, individual behavior in maintaining personal hygiene and health is a major factor in cutting the covid-19 chain. Muara Batun is one of the villages in Jejawi District, OKI Regency, South Sumatra which is included in the yellow zone (low risk) in the spread of Covid-19. Since the implementation of the adaptation of new normal, the awareness of residents to implement health regulations during the pandemic has been violated a lot. The purpose of this activity is to regenerate awareness, increase participation and participation of citizens in bypassing the covid-19 chain with the PHBS approach. The method of this activity uses the Partner Village Development (PPDM) model in the form of community empowerment by implementing interprofessional interventions based on Interprofessional Collaboration (IPC) and the Inter Professional Education (IPE) approach. The results of this activity have had a positive impact. A joint commitment between citizens and stakeholders is needed in cutting the covid-19 chain, one of which is the willingness of each individual to adopt good habits adopted from good behavior during the pandemic and willing to become agents of change to invite other individuals to cultivate PHBS in their daily lives.